2005
DOI: 10.1111/j.1600-6143.2005.00830.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of an Early Protocol Biopsy in Living-Donor Renal Transplantation: Ten-Year Experience at a Single Center

Abstract: We report here our 10-year experience of a biopsy performed at day 14 after transplantation in 304 patients with stable graft function. The factors that may have influenced subclinical rejection were analyzed according to histology. The incidence of subclinical rejection was 13.2%. Addition of mycophenolate mofetile (MMF) as a primary immunosuppressant significantly decreased the incidence of subclinical rejection compared with patients without such treatment (odds ratio, 0.23; p < 0.05). On the other hand, HL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
120
1
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(131 citation statements)
references
References 27 publications
9
120
1
1
Order By: Relevance
“…In the Winnipeg studies, the prevalence of subclinical rejection in protocol biopsies that were performed at 1, 2, and 3 mo was 0, 25, and 20%; 32, 32, and 30%; and 30, 37, and 63% in zero, one, and two HLA-DR mismatched patients, respectively (25). A correlation between HLA mismatches and the prevalence of subclinical rejection has been reported also by others (10,14). Moreover, our group found that subclinical rejection is more prevalent in patients who are presensitized to class I or class II HLA antigens as detected by flow cytometry (26).…”
Section: Risk Factors For Subclinical Rejectionmentioning
confidence: 91%
See 2 more Smart Citations
“…In the Winnipeg studies, the prevalence of subclinical rejection in protocol biopsies that were performed at 1, 2, and 3 mo was 0, 25, and 20%; 32, 32, and 30%; and 30, 37, and 63% in zero, one, and two HLA-DR mismatched patients, respectively (25). A correlation between HLA mismatches and the prevalence of subclinical rejection has been reported also by others (10,14). Moreover, our group found that subclinical rejection is more prevalent in patients who are presensitized to class I or class II HLA antigens as detected by flow cytometry (26).…”
Section: Risk Factors For Subclinical Rejectionmentioning
confidence: 91%
“…Our current definition of subclinical rejection requires that the serum creatinine be increased by Ͻ10% 2 wk before the protocol biopsy and that the histologic Banff score is "ai2at2" (type IA acute rejection) or greater. Numerous groups since have confirmed the occurrence of subclinical rejection as defined above, in both adults (7)(8)(9)(10)(11)(12)(13)(14) and children (15,16). Some investigators include "borderline" rejection (Banff score Ͻai2at2) in the subclinical rejection category (7,9 -11,14).…”
Section: Subclinical Rejection: Prevalence Risk Factors and Signifimentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, in a 10-yr study of 304 patients with stable graft function, those with borderline changes or SCR in protocol biopsy specimens at 14 d posttransplantation were found to have a higher incidence of acute rejection than those with normal biopsies (0.48 and 0.60 versus 0.23, respectively; P Ͻ 0.05) (10). Moreover, the graft survival rates in patients with SCR in day 14 biopsies in this study were lower than those with normal or borderline changes at 1 yr (88.4 versus 97.9 and 99.1%; P Ͻ 0.05), 5 yr (77.8 versus 96.2 and 95.9%; P Ͻ 0.05), and 10 yr (62.3 versus 96.2 and 93.7%; P Ͻ 0.05).…”
Section: Detection Of Subclinical Rejectionmentioning
confidence: 99%
“…Thus, early inflammation detected in protocol biopsies predicts progression of renal fibrosis and shorter renal allograft survival (248)(249)(250).…”
Section: Key Molecular Effector Systems and Therapies In Renal Fibrosismentioning
confidence: 99%